Do clinical practice guidelines for the prevention of pressure ulcers really prevent pressure ulcers? An analysis of the guidelines - Sharp, Catherine (Asian Journal of Medical Sciences, 2022)
This review article aims to analyze sections of the 2012 Australian Wound Management Association, Pan Pacific, Clinical Practice Guideline for the Prevention and Management of Pressure Injury, the “Guide,” mandated for use in all Australian residential aged care facilities to explain why pressure ulcers still occur, I considered two sections of the “Guide:” a) “Assess all patients as soon as possible following admission to service and within a minimum of 8 h;” and b) “Implement a prevention plan – strategies for patients at high risk: Use a high specification foam reactive (constant low pressure) support surface OR consider using an (active alternate pressure) support surface.” Nowhere in the “Guide” is there an explanation for a) “Assessing all patients as soon as possible following admission and within a minimum of 8 h.” Similarly, there is no explanation for why b) “a high specification foam reactive (constant low pressure) support surface” is recommended to prevent pressure ulcers. The evidence for screening “within a minimum of 8 h,” does not consider the speed at which pressure ulcers develop. If the resident is lying in one position for 30 min or more and a “constant low pressure” mattress is used, residents may still develop pressure ulcers because a “constant low pressure” does not relieve pressure.